Territorialities and Urbanities Transform: A Scenario-Based Approach to Local Planning and Decision Making in Inukjuak and Salluit, Nunavik - Vachon, Geneviève; Avarello, Mathieu; Landry, Julien; St-Jean, Laurence (Études Inuit Studies, 2020)
This article focuses on the sustainable transformation of Nunavik’s Northern Villages with regard to the notions of dwelling, urbanity and territoriality. Our participatory design research approach addressed the limits of current planning frameworks, exogenous development models, and a complex governance system by integrating the relationship to the territory and the impacts of climate change in the exploration of scenarios for alternative futures adapted to local urban realities. The research illustrates these limits and complexities with hypothetical transformation scenarios in Inukjuak and Salluit. By identifying plausible futures, we formulated sustainable planning strategies combining interrelated factors in the development of project-based interventions to incorporate traditional practices in an urbanizing context. The case of Inukjuak illustrates the importance of natural environments, urban consolidation practices, diversity of use, and socialization, while that of Salluit demonstrates the reciprocity between geomorphological, constructive, socio-cultural, and logistical design variables. Evolving Northern development challenges require that the relevance of these scenarios be examined based on alternative hypotheses and long-term horizons, in the imagination of shared strategies for sustainable planning. Design research, the use of decision-making tools and participatory frameworks are questioned in relation to their contribution to the self-determination of local communities in the “resituation” of their living environments.